2019
DOI: 10.1016/j.landurbplan.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing post-disaster resilience by ‘building back greener’: Evaluating the contribution of nature-based solutions to recovery planning in Futaba County, Fukushima Prefecture, Japan

Abstract: This research evaluates the contribution of nature-based solutions to urban resilience in postdisaster situations. Post-disaster recovery planning is an opportunity to 'build back greener' by fostering ecosystem approaches towards social and ecological resilience. Yet understanding of specific post-disaster resilience benefits which nature-based solutions provide is still emerging. This paper contributes to this field through evaluation of how ecosystem approaches bring resilience benefits in Futaba County, Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 43 publications
(52 reference statements)
0
26
0
1
Order By: Relevance
“…Urban and peri-urban natural areas have been shown to be important in ‘normal’ times [ 57 , 58 ] and in times of crisis [ 20 , 21 ] and upheaval [ 22 ]. The popular press has touted the importance of outdoor space and nature in these globally stressful times [e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urban and peri-urban natural areas have been shown to be important in ‘normal’ times [ 57 , 58 ] and in times of crisis [ 20 , 21 ] and upheaval [ 22 ]. The popular press has touted the importance of outdoor space and nature in these globally stressful times [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As millions of Americans lost their jobs and were pushed into food insecurity, some relied on their urban greenspaces to provide sustenance and a mental escape from the stressful times [ 20 ]. Following the 2011 earthquake, tsunami and nuclear disaster in Futaba County, Japan, city officials have made it a point to rebuild key green spaces that provide cultural ecosystems services crucial to the recovery of locals [ 21 ]. These green spaces are crucial to providing a sense of pride and identity for residents as they recover from this disaster [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that while the hard defenses in China provide 3.18 million per km on average for TC-related protection, coastal wetlands outweigh these hard defenses as they are more cost-effective. Similarly, adopting natural solutions to risk mitigation has been recognized as a progressive way-out globally (Temmerman et al, 2013;Sajjad et al, 2018;Mabon, 2019). Hence, adopting nature-based urban development or hybrid approaches (integrated natural and engineered) in Hong Kong should be explored and considered to cope with the increasing damages from TCs rather engineering-based defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the green belt can effectively prevent road surface water and further reduce the economic losses caused by storm surge disasters. So, the green plant plays a vital role in social, ecological, and economic recovery after disasters such as hurricanes [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%